Against erosion of labour standards: global reorganisation of value chains and industrial relations in the European motor industry. (1st April 2010) - ,; ,
Abstract : This paper analyses the impacts of globalisation on the systems of industrial relations in the motor industry in a comparative perspective. Globalisation, in the form of the global reorganisation of the value chain, has been a key development in this industry since the 1990s. This development has been characterised by the creation of global production networks at the Original Equipment Manufacturers (OEMs), the final producers, the internal reorganisation of the companies, involving higher productive flexibility, decentralisation and financialisation, and the restructuring of the value chain, involving a reduction of vertical integration and new forms of network relationships between OEMs and their suppliers. These developments raise a number of questions: Are regime competition and reorganisation undermining national or industry labour standards? What types of standards are in danger and to what extent? Or are there existing or emergent counter forces that can weaken or even prevent a process of erosion of these standards? In order to address these questions, this paper investigates the contents, forms and levels of collective agreements, the roles and strategies of the actors in collective bargaining and possible fragmentations along the value chain. This is achieved by means of a comparative analysis of the developments in four countries: Germany, Italy, Spain and Hungary.